1963 International Meetings (Academy of Management Journal, 1963)
A calender of events related to the Academy of Management during the year of 1963 is presented. The International Chamber of Commerce will hold its Biennial Congress in April. The European Accountancy Organizations Congress will take place in September. The International Union of Christian Employers's Biennial Conference will be held in October.